Salt‐enhanced cultivation as a morphology engineering tool for filamentous actinomycetes: Increased production of labyrinthopeptin A1 in Actinomadura namibiensis - Tesche, Sebastian; Rösemeier‐Scheumann, René; Lohr, Jonas; Hanke, René; Büchs, Jochen; Krull, Rainer (Engineering in life sciences, 2019)
Salt‐enhanced cultivation as a morphology engineering tool for the filamentous actinomycete Actinomadura namibiensis was evaluated in 500‐mL shaking flasks (working volume 100 mL) with the aim of increasing the concentration of the pharmaceutically interesting peptide labyrinthopeptin A1. Among the inorganic salts added to a complex production medium, the addition of (NH4)2SO4 led to the highest amount of labyrinthopeptin A1 production. By using 50 mM (NH4)2SO4, the labyrinthopeptin A1 concentration increased up to sevenfold compared to the non‐supplemented control, resulting in 325 mg L−1 labyrinthopeptin A1 after 10 days of cultivation. The performance of other ammonium‐ and sulfate‐containing salts (e.g., NH4Cl, K2SO4) was much lower than the performance of (NH4)2SO4. A positive correlation between the uptake of glycerol as one of the main carbon sources and nongrowth‐associated labyrinthopeptin productivity was found. The change in the cell morphology of A. namibiensis in conjunction with increased osmolality by the addition of 50 mM (NH4)2SO4, was quantified by image analysis. A. namibiensis always developed a heterogeneous morphology with pellets and loose mycelia present simultaneously. In contrast to the non‐supplemented control, the morphology of (NH4)2SO4‐supplemented cultures was characterized by smaller and circular pellets that were more stable against disintegration in the stationary production phase.